Game RPG Matematika Berbasis Fuzzy Mamdani-DDA dan Dasbor Guru untuk Sekolah Dasar - Yulyanto; Muhammad Nauval Bintang; Rio Andriyat Kridiawan (Forum Kerjasama Pendidikan Tinggi (FKPT), 2026)
This study develops and evaluates the feasibility of “Jiwa Menghitung,” an Android turn-based RPG for elementary school mathematics (Grades 4–6). The principal novelties are: (1) adoption of Fuzzy Mamdani inference—rather than Sugeno—as the DDA engine, yielding linguistically interpretable categorical outputs (Easy/Medium/Hard) directly communicable to educators; and (2) a dual-sided architecture integrating the game client with a real-time teacher dashboard via Firebase. The Mamdani engine, governed by nine IF-THEN rules and Centroid of Gravity (COG) defuzzification, adapts question difficulty from two inputs: player response time and error count. Membership function parameters were validated through expert review by two mathematics teachers, and the rule base verified by white-box analysis (V(G)=3). User Acceptance Testing (UAT) with 42 students yielded 90.98% overall acceptance (Usability: 95.35%; DDA System: 80.00%), while teacher UAT (n=2) produced 88.09%—both exceeding the “Very Feasible” threshold. N-gain analysis for Grades 4 and 5 produced moderate gains (g=0.36 and g=0.34), while Grade 6 exhibited a ceiling effect identifying a critical design constraint. Findings confirm the technical feasibility and user acceptance of Mamdani-based DDA, while establishing adaptation granularity as a key development priority.